Analisis Biaya Promosi Pada PT. Bangun Karawang Megah - Nuke Betharini; Dedi Mulyadi; Santi Pertiwi Hari Sandi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
With the increasing need for housing in Karawang, PT. Bangun Karawang Megah saw a promising opportunity and decided to build housing in response to increasing demand. To market this housing project, PT. Bangun Karawang Megah plans a careful promotional strategy. This research aims to find out how promotional costs can increase revenues at PT. Build a Magnificent Karawang. The method uses descriptive qualitative techniques using interview data collection and literature studies related to the research variables. The results that were published based on the interviews that had been conducted were PT. Bangun Karawang Megah uses various platforms to promote its housing such as Instagram, brochures, banners and billboards. The company also provides special service to customers with additional offers in the form of free aluminum frames, washing machines and back covers. The conclusion obtained based on interviews that have been conducted is the importance of promotion via Instagram. Anjar Septianto's involvement as a brand ambassador proves that investment in public figures can provide a 28.49% increase in sales in August, even though the cost of promotion using a brand ambassador is relatively low, only Rp. 2. 500,000, but this promotion proved to be very profitable because it succeeded in increasing revenue from IDR 8,748,000,000 to IDR 20,250,000,000 and this revenue became the highest revenue obtained by the company in 2023.